Private Participation in the Management of Water Resources According to Law Number 17 of 2019 concerning Water Resources - Musthofa , Arafat Nasrulloh; Roestamy, Martin; Fulazzaky , Mohamad Ali (Universitas Djuanda, 2024)
Water is a primary human need that God has given to all His creatures. Water is a source of needs and fulfillment of many people's needs. The management of water resources is held by the government to be used for the welfare of citizens according to the mandate of the 1945 Constitution. The research objectives are as follows: 1. To find out and analyze the tasks of the central government in dividing the management of natural resources both for the community and for private companies. 2. To find out and analyze the role of the private sector in water resources according to Law no. 17/2019 concerning Water Resources. The method is normative juridical study with qualitative approach using primary and secondary data. The results of the research are that water resources management involves various parties which often conflict and cause conflict. Therefore, good coordination is needed to unite the interests of the community and the government to produce an effective and efficient formulation of water resources management. The government plays a very important role in managing water resources so that all people get clean water in a fair and equitable manner to meet their daily needs. Keywords : Private, Management, Water